Co2P quantum dot embedded N, P dual-doped carbon self-supported electrodes with flexible and binder-free properties for efficient hydrogen evolution reactions. Issue 6 (25th January 2018) - Zhang, Chengtian; Pu, Zonghua; Amiinu, Ibrahim Saana; Zhao, Yufeng; Zhu, Jiawei; Tang, Yongfu; Mu, Shichun
Abstract : Co2 P quantum dots embedded in N, P dual-doped carbon on carbon cloth, as hydrogen evolution reaction (HER) electrode, present superb activity and stability. Abstract : Transition metal phosphides (TMPs) are considered to be superb catalysts for water splitting. In this work, we introduce an efficient strategy to fabricate dicobalt phosphide (Co2 P) quantum dots embedded in N, P dual-doped carbon (Co2 P@NPC) on carbon cloth (Co2 P@NPC/CC) by in situ carbonization of cobalt ion induced phytic acid (PA) and polyaniline (PANI) macromolecule precursors. As a highly efficient self-supported electrode, it has a low onset overpotential (74 mV at 1 mA cm −2 ) approaching that of the commercial Pt/C catalyst for the hydrogen evolution reaction (HER) in acidic media. Meanwhile, it also shows very low overpotentials of only 116 and 129 mV at 10 mA cm −2 with robust stability in acidic and alkaline media, respectively.